The preparation and use of metal salen complexes derived from cyclobutane diamine - Patil, Smita S. (Kansas State University, 2014)
The helix is an important chiral motif in nature, there is increasing development in field of helical transition metal complexes and related supramolecular structures. Hence, the goals of this work are to apply the principles of helicity in order to produce metal complexes with predictable molecular shapes and to study their properties as asymmetric catalysts. Computational studies suggest that the (1R,2R)-cyclobutyldiamine unit can produce highly twisted salen complexes with a large energy barrier between the M and P helical forms. To test this prediction, the tartrate salt of (1R,2R)-cyclobutyldiamine was synthesized and condensed with a series of saliclaldehydes to produce novel salen ligands. The salicylaldehydes chosen have extended phenanthryl or benz[a]anthryl sidearms to encourage formation of helical coordination complexes. These ligands were metallated with zinc, iron and manganese salts to produce salen metal complexes which were characterized by NMR analysis, high-resolution mass spectrometry, and IR spectroscopy. A second ligand type, neutral bis(pyridine-imine) has also been synthesized from (1R,2R)-cyclobutyldiamine and quinolylaldehydes. The synthesis of bis(pyridine-imine) ligands was conducted using greener method, solvent assisted grinding. These ligands, in-situ with nickel metal salts, showed good catalytic activity for asymmetric Diels-Alder reactions. The third ligand type studied was chiral acid-functionalized Schiff-base ligands. These were synthesized by the condensation of 3-formyl-5-methyl salicylic acid and (1R,2R)-cyclobutyldiamine. With this type of ligand, there is possibility of producing both mono and dinuclear metal complexes. In our studies, we were only able to synthesize mononuclear complexs. These were tested as catalysts for asymmetric direct Mannich-type reaction, but were found to be ineffective.
Keywords: Transition metal complex; Asymmetric catalysis; Salen ligands; Chemistry (0485)